Do correlated defaults matter for CDS premia? An empirical analysis - Christian Koziol; Philipp Koziol; Thomas Schön (Deutsche Bundesbank, 2014)
Correlated defaults and systemic risk are clearly priced in credit portfolio securities such as CDOs or index CDSs. In this paper we study an extensive CDX data set for evidence whether correlated defaults are also present in the underlying CDS market. We develop a cash flow based top-down approach for modeling CDSs from which we can derive the following major contributions: (I) Correlated defaults did not matter for CDS prices prior to the financial crisis in 2008. During and after the crisis, however, their importance has increased strongly. (II) In line with a plausible default order, we observe that correlated defaults primarily impact the CDS prices of firms with an overall low CDS level. (III) Idiosyncratic risk factors for each single CDS play a major (minor) role when the CDS premia are high (low).
Keywords: G14; G21; 330; Correlated Defaults; Systemic Risk; Idiosyncratic Risk; Collateralized Debt Obligations; Credit Default Swaps; Credit Derivatives